Makers of modern strategy : military thought from Machiavelli to Hitler / edited by Edward Mead Earle, Gordon A. Craig and Felix Gilbert - Earle, Edward Mead ; Craig, Gordon A ; Gilbert, Felix (Princeton University Press, 1948)
553 halaman ; 24 cm